বাংলাদেশের ছোটগল্প : বিষয়- ভাবনা স্বরূপ ও শিল্পমূল্য - আজাহার ইসলাম. (ঢাকা : বাংলা একাডেমী, 1996)
A critical perspective of the 20th century Bengali short stories from Bangladesh.
Includes bibliographical references (p. [651]-656) and index.
In Bengali.
Keywords: Short stories, Bengali -- Bangladesh -- History and criticism; Bengali fiction -- 20th century -- History and criticism